PENGARUH LAMA APLIKASI DAN WAKTU PERENDAMAN GIGI DENGAN JUS BUAH PIR TERHADAP PERUBAHAN WARNA DAN KEKERASAN MIKRO - Dewi Ratma Utami; Andina Rizkia Putri Kusuma; Welly Anggarani (Odonto : Dental Journal, 2016)
Background: Teeth discoloration is considered disturbing performance,therefore bleaching become an option for teeth whitening. Hydrogen Peroxide (H2O2) is commonly used, it is beneficial for teeth whitening but in other hand it has adverse effectin lowering micro hardness of the tooth. Hydrogen Peroxide can be found in pears. The objectives of this research were to determine the influences of application duration and immersion time of tooth when immersed in pear juice toward its discoloration and micro hardness.Method: An experimental study with pre-post test controlled group design were conducted using 28 premolars teeth which divided into four groups. Group A and Bwere immersed in pear juice with concentration of 100% for 30 and 60 minutes/day. Group C and D were immersed in H2O2 3% for 30 and 60 minutes/day each for 14 days. Tooth color and micro hardness of each tooth sample were recorded before and on 7thand 14thdays after immersion. The data was analyzed by friedman test, repeated anova, one-way anova and post hoc.Result: The average of tooth color index based on the duration of application in all four groups showed significant changes, while the average change in micro hardness index based on the duration of applications were shown significant difference only in group C and D. The difference of time immersion in pear juice 100% for 30 and 60 minutes had no effect on tooth discoloration and micro hardness.Conclusion: It can be concluded that pear juice can be used as an alternative material for bleaching process without deteriorating it’s micro hardness.